2015
DOI: 10.1007/s11325-015-1229-4
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on the relationships among the polymorphism of period2 gene, work stress, and insomnia

Abstract: The effect of genotype AC or allele C of Per2 on insomnia was relatively stronger than that of high work stress, suggesting that individual's susceptibility should be taken into consideration when intervening and controlling insomnia of workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…For instance, a significant association between Per3 and insomnia was described by Brower and coworkers (2012) [22]. Similar findings were found when period 2 gene (Per2) was associated with insomnia [23]. Another gene candidate related to insomnia has been the serotonin transporter polymorphic region (5-HTTLPR), adenosine, GABA and orexin/hypocretin [18].…”
Section: Genes and Insomniasupporting
confidence: 56%
“…For instance, a significant association between Per3 and insomnia was described by Brower and coworkers (2012) [22]. Similar findings were found when period 2 gene (Per2) was associated with insomnia [23]. Another gene candidate related to insomnia has been the serotonin transporter polymorphic region (5-HTTLPR), adenosine, GABA and orexin/hypocretin [18].…”
Section: Genes and Insomniasupporting
confidence: 56%
“…Although not explicitly focused on insomnia, several of the first studies examined the role of circadian genes ( CLOCK , Timeless ) and sleep in individuals with mood disorders, with mixed results [43,44,45]. More recent work has been in the Per genes, with a Chinese study finding a significant association between Per2 genotype and insomnia, as well as a G×E interaction with Per2 , work stress, and insomnia [46]. Another paper, examining Per3 and insomnia in individuals with alcohol dependence, also found a significant genotype effect [47].…”
Section: Measured Gene Studies Of Insomniamentioning
confidence: 99%
“…Furthermore, researchers examined the main effects of genetic factors on sleep, but they had incongruent outcomes (Barclay, Eley, Mill, et al, 2011; van Dalfsen & Markus, 2019; Huang et al., 2014). More interestingly, recent studies showed interactions between serotonin transporter‐gene‐linked polymorphic region ( 5‐HTTLPR ), CLOCK , period 3 ( PER3 ), and PER2 gene polymorphisms and stress on sleep (Antypa et al, 2012; Huang et al., 2014; Li, Huang, Lan, & Wang, 2015). This kind of gene–environment interaction has been suggested to be able to produce robust genetic results, as it focussed on homogenous environmental subsets and thus reduced the aetiological heterogeneity (Wray et al., 2012).…”
Section: Introductionmentioning
confidence: 99%